2007
DOI: 10.1063/1.2811870
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced breakdown spectroscopy of trisilane using infrared CO2 laser pulses

Abstract: Synthesis and photoluminescence of fluorinated graphene quantum dots Appl. Phys. Lett. 102, 013111 (2013) The luminescence characteristics of CsI(Na) crystal under α and X/γ excitation J. Appl. Phys. 113, 023101 (2013) Structural and optoelectronic properties of Eu2+-doped nanoscale barium titanates of pseudo-cubic form J. Appl. Phys. 112, 124321 (2012) Quantum yield of luminescence of Ag nanoclusters dispersed within transparent bulk glass vs. glass composition and temperature Appl. Phys. Lett. 101, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…A doublet due to the 3s 2 4p 2 P 1/2,3/2 → 3s3p 2 2 D 3/2,5/2 transitions at 385.71 and 386.37 nm, a strong doublet of Si II lines at 413 nm due to the 3s 2 4f 2 F 5/2,7/2 → 3s 2 3d 2 D 3/2,5/2 transitions, a doublet due to the 3s 2 4d 2 D 3/2,5/2 → 3s 2 4p 2 P 1/2,3/2 transitions at 504.24 and 505.74 nm and another doublet due to the 3s 2 4p 2 P 1/2,3/2 → 3s 2 4s 2 S 1/2 transitions at 634.89 and 637.31 nm which lies adjacent to the hydrogen Hα line at 656.28 nm. Camacho et al [16] reported the LIBS spectra of silicon using a CO 2 who observed a number of neutral silicon lines in addition to some lines due to singly and doubly ionized silicon ions. Four Si + doublets (see above) have been observed but two doublets reported by Camacho et al [16] around 596 nm and around 536 nm are absent; may be too weak to be observed under the present experimental conditions.…”
Section: The Emission Spectrummentioning
confidence: 99%
See 3 more Smart Citations
“…A doublet due to the 3s 2 4p 2 P 1/2,3/2 → 3s3p 2 2 D 3/2,5/2 transitions at 385.71 and 386.37 nm, a strong doublet of Si II lines at 413 nm due to the 3s 2 4f 2 F 5/2,7/2 → 3s 2 3d 2 D 3/2,5/2 transitions, a doublet due to the 3s 2 4d 2 D 3/2,5/2 → 3s 2 4p 2 P 1/2,3/2 transitions at 504.24 and 505.74 nm and another doublet due to the 3s 2 4p 2 P 1/2,3/2 → 3s 2 4s 2 S 1/2 transitions at 634.89 and 637.31 nm which lies adjacent to the hydrogen Hα line at 656.28 nm. Camacho et al [16] reported the LIBS spectra of silicon using a CO 2 who observed a number of neutral silicon lines in addition to some lines due to singly and doubly ionized silicon ions. Four Si + doublets (see above) have been observed but two doublets reported by Camacho et al [16] around 596 nm and around 536 nm are absent; may be too weak to be observed under the present experimental conditions.…”
Section: The Emission Spectrummentioning
confidence: 99%
“…Camacho et al [16] reported the LIBS spectra of silicon using a CO 2 who observed a number of neutral silicon lines in addition to some lines due to singly and doubly ionized silicon ions. Four Si + doublets (see above) have been observed but two doublets reported by Camacho et al [16] around 596 nm and around 536 nm are absent; may be too weak to be observed under the present experimental conditions. In addition, not a single line due to doubly ionized silicon has been detected.…”
Section: The Emission Spectrummentioning
confidence: 99%
See 2 more Smart Citations
“…For laser ablation of carbon, OES studies in different atmospheres are reported and these studies have yielded many interesting results . Detailed studies of laser-induced breakdown spectroscopy on N 2 and Si 3 H 8 in the gas phase have been recently made in our laboratory [32,33].…”
Section: Introductionmentioning
confidence: 99%